Investigating COVID-19 Health Seeking and Health Information Seeking During Alert Level 4, 2020: A Qualitative Descriptive Study of Laotian New Zealanders in Auckland, New Zealand - Nedthongsavanh, Phoutthanaphone (Auckland University of Technology, 2021)
Risk communication is a key element of effective epidemic and pandemic response. The COVID-19 pandemic has underlined the crucial role of risk communication to guide the public health response during this complex, global public health emergency. Recognising the limited research on risk communication in public health emergencies as this applies to migrant and ethnic minorities, this study sought to investigate Laotian New Zealanders’ COVID-19 health seeking and health information seeking during Alert Level 4 or “lockdown” conditions in Auckland, New Zealand. The study applied a qualitative descriptive approach which was underpinned by interpretivism and adopted semi-structured interviews as the data gathering method. Despite the challenges of the COVID-19 pandemic, face-to-face interviews were carried out with 10 Laotian New Zealanders residing in Auckland in 2021. Thematic analysis and a coding process using NVivo software identified three main themes related to health seeking and health information seeking: 1) the socio-economic characteristics and family profile; 2) individual capability and self-beliefs; and 3) exposure to diverse information sources. The findings highlighted five important issues. These included the role of socio-economic factors and family profile in informing participant preferences for specific COVID-19 health information sources. They also reflected the importance of improving certainty and stability in participants’ lives through work subsidies to reduce the impact of disrupted employment and income. Study results highlighted the relationship between trust in public authorities and self-efficacy in implementing public health advice, and the importance of preserving and protecting the stability of existing health services in times of public health emergency. They underlined the complex role of transboundary information sources and the need to manage this more effectively. Study results highlight the need for continuing research with migrants and ethnic minorities to strengthen risk communication and community engagement with these vulnerable, but resourceful populations. It also calls for research to examine how online and geographic communities influence information-seeking and healthcare seeking during public health emergencies.
Keywords: Migrants; Asylum seekers; Laotians; Laos; Laotian; Lao; Immigrants; Refugees; Emergency risk communication; Health information; Healthcare-seeking behaviours; Risk communication; Public health emergency; International health regulations; Epidemic; Pandemics; Auckland; New Zealand; COVID-19; The COVID-19; Alert Level 4; Lockdown; Qualitative descriptive; Qualitative study; ASEAN; Asian migrants; Asian; Restrictions